Nexus between energy poverty and economic vulnerability: Evidence from low and middle income economies. Issue 1 (31st December 2022) - Nguyen, Canh Phuc; Dinh Thanh, Su
ABSTRACT: Energy poverty is one of the important facets of sustainable development, but less attention to the linkage of energy poverty to economic vulnerability. This study proposes that two variables would have a mutual linkage, which is tested through a sample of 73 low- and middle-income economies. By applying panel Granger causality and two-step system generalised method of moments estimate to a system equation of two variables, the robust results are as follows. First, mutual causalities between economic vulnerability and energy poverty are evidenced. Second, economic vulnerability appears to have an increased influence on energy poverty; and energy poverty, in return, shows similar effects on economic vulnerability. Third, the nexus is mostly consistent in 46 low- and lower-middle-income economies and 27 upper-middle-income economies. The results indicate the important mutual link between economic vulnerability and energy poverty at a global level, which demands urgent action on appropriate policies to deal with energy poverty